Design and experiment of human hand motion driven electromagnetic energy harvester using dual Halbach magnet array. (7th February 2017) - Salauddin, M; Park, Jae Y
Abstract: We present a dual Halbach array electromagnetic energy harvester that generates significant power from hand shaking vibration. The magnetic-spring configuration is employed for generating sufficient power from the hand motion of irregular and low-frequency vibrations. However, significant power generation at low-frequency vibrations is challenging because the power flow decreases as the frequency decreases; moreover, designing a spring-mass system that is suitable for low-frequency-vibration energy harvesting is difficult. In this work, our proposed device overcomes both of these challenges by using a dual Halbach array and magnetic springs. During the experiment, vibration was applied in a horizontal direction to reduce the gravity effect on the Halbach-array structure. To achieve an increased power generation at low-amplitude and low-frequency vibrations, the magnetic structure of the dual Halbach array and the magnetic springs were optimized in terms of the operating frequency and the power density. A prototype was fabricated and tested both using a vibration exciter and by manual hand-shaking. The fabricated device showed resonant behavior during the vibration exciter test. For the vibration exciter test, the prototype device offers a maximum average power of 2.92 mW to a 62 Ω optimum load, at a 6 Hz resonance frequency and under a 0.5 g acceleration. The prototype device is capable of delivering a maximum average power of 2.27 mW from hand shaking. The fabricated device exhibited a normalized power density 0.46 mW cm −2 g −2 which is very high compared to the current state-of-the-art devices, representing its ability in powering portable and wearable smart devices from extremely low frequency vibration.